BUDAYA BIROKRASI EWUH PAKEWUH DAN KECURANGAN AKUNTANSI DI PEMERINTAHAN : PERSEPSI APARAT PENGAWAS INTERNAL PEMERINTAH (APIP) INSPEKTORAT KABUPATEN SRAGEN - Ratna Fatmawati (STIE AUB Surakarta, 2016)
device implementing governance in which APIP is located. APIP position Inspectorate in preventing or uncovering the accounting fraud is very strategic, but in the execution of their duties often appears cheekily to reveal or discover the accounting fraud that occurs if the auditee has a As we know an organization covering culture and structure. During this time more focused on the improvement of the organizational structure rather than the culture contained in the organization. Yet in reality the culture can affect the organizational structure. Cultures were examined in this study is a bureaucratic culture” ewuh-pakewuh” accounting and the accounting fraud that occurred in local government, seeing the possibility of a correlation between a bureaucratic culture with a tendency ewuh-pakewuh accounting fraud.